Psychoactive substance consumption and criminality among commercial drivers in selected motor parks in Ibadan metropolis, Oyo State (2023)
Substance consumption is a major issue that has taken a deep root in our society. This study examined the effect of substance consumption among commercial drivers in selected parks in Ibadan metropolis. The study employed a descriptive survey design and a multistage sampling technique was also used to select two modem parks at Ojoo and Challenge in Ibadan while simple random sampling was used to select 188 commercial drivers at the two parks. A structured questionnaire was used to gather information from the respondents. The data collected were analysed using simple percentage and frequency counts while Pearson Product Moment Correlation (PPMC) statistical package was used to analyse the hypotheses. Findings revealed that the correlation between substance use and reasons for substance use was not significant but positive and low [0.068 (0.352)] which indicate that substances were taken on account of getting high and to remain awake while driving. Also, the correlation between substance use and implications for substance use was significant but negative and low [-0.228 (0.002)]. Findings also showed that the correlation between substance use and measures for eradicating substance use was not significant as well as negative and low [-0.101 (0.169] which means measures were not enforced by the government agency, hence, rules were not adhered to. The study recommends that government agency should develop a device for testing drivers who test positive to any substances, also, the state and local governments should enact laws and sanction any commercial drivers caught abusing substances